Benefit of Filgotinib, a JAK1 Preferential Inhibitor, in Rheumatoid Arthritis Patients with Previous Rapid Radiographic Progression: Post Hoc Analysis of Two Trials - Yoshiya Tanaka; Tatsuya Atsumi; Daniel Aletaha; Beatrix Bartok; Alena Pechonkina; Ling Han; Kahaku Emoto; Shungo Kano; Vijay Rajendran; Tsutomu Takeuchi (Rheumatology and Therapy, 2022)
Abstract Introduction We conducted a post hoc analysis of efficacy and safety of filgotinib stratified by estimated radiographic progression rate before baseline (BL) in patients with rheumatoid arthritis (RA) who had inadequate response to methotrexate (MTX; FINCH 1; NCT02889796) or were naïve to it (FINCH 3; NCT02886728). Methods Radiographic progression rate was BL-Modified Total Sharp Score (mTSS) divided by RA duration (BL mTSS/year); estimated rapid radiographic progression (e-RRP) was BL change in mTSS/year ≥ 5; and estimated nonrapid radiographic progression (e-NRRP) was BL mTSS/year < 5. Efficacy and safety were compared between subgroups. All p-values are nominal. Results In FINCH 1 and FINCH 3, 558/1755 (31.8%) and 787/1249 (63.0%) patients, respectively, had BL e-RRP. BL characteristics were generally similar between subgroups within each trial. At week (W) 24, in FINCH 1, proportions achieving a Disease Activity Score 28 for rheumatoid arthritis with C-reactive protein  < 2.6 were significantly greater with filgotinib 200 (FIL200) and 100 mg (FIL100) versus placebo among e-RRP and e-NRRP subgroups. In each study, proportions of FIL-treated patients achieving Clinical Disease Activity Index ≤ 2.8 and Simple Disease Activity Index ≤ 3.3 were similar between subgroups. In FINCH 3, disease activity measures were at least numerically improved among patients receiving FIL versus MTX monotherapy. At W24, mTSS changes from BL (CFB) were greater among patients with e-RRP in FINCH 1 and FINCH 3 versus e-NRRP (0.81 versus 0.19, p = 0.001; 0.67 versus 0.25, p = 0.31, respectively). At W52, in FINCH 1, mTSS CFBs were smaller among e-RRP patients treated with FIL200 (0.40; p < 0.001) and FIL100 (0.77; p = 0.024) versus adalimumab (ADA; 1.46). In FINCH 3 at W52, mTSS CFBs were significantly smaller with FIL200 versus MTX among e-RRP patients. Rates of treatment-emergent adverse events (AEs) were comparable between subgroups and across treatment arms. Conclusions Patients with previous e-RRP who received standard care tended to progress radiographically. FIL200 demonstrated persistent, consistent benefit for disease activity control among e-RRP and e-NRRP subgroups, and AE profiles were similar between subgroups. Although filgotinib efficacy was somewhat reduced among patients with e-RRP, filgotinib treatment slowed radiographic progression in both subgroups. Trial Registration Clinicaltrials.gov NCT02889796, NCT02886728.